ANALISIS SISTEM PERAWATAN KOMPONEN GENERATOR STARTER PADA MESIN PESAWAT DI PT XYZ - Sudri, Ni Made; Nendissa, Bendjamin Ch; Herawati, Yuli (Teknik dan Ilmu Komputer, 2012)
The implementation of planned and preventative maintenance is essential to the operation of aircraft engines so that failures can be prevented. The case study in PT XYZ reveals that the engine starter generator has an important function for the activation during the operation. The short brush component has the highest damage frequency among other components in the starter generator (approximately 63.16%). The Mann test results claimed that the failure of short brush was Weibull distributed with MTTF value ofÃÂ 329.674. In order to maintain the reliability of the machine, it is suggested thatÃÂ performing routine maintenance and replacing critical components prior to the MTTF should be done. Spare parts need to be prepared with an appropriate standard of care.ÃÂ Keywords:ÃÂ predictive maintenance, realiability engineering, MTTFÃÂ